Strategy To Build Public Awareness In Preventing Online Fraud Crimes In The Jurisdiction Of The Cimahi Police - Agus Setyawan; Chairul Muriman Setyabudi; Surya Nita (Ridwan Institute, 2023)
This research is motivated by the negative impact of the development of information technology, especially the internet, which has caused an increase in cases of cyber crime. The number of victims in this type of crime is partly triggered by low public awareness. Therefore, this research is aimed at explaining appropriate strategies for building public awareness in preventing online fraud crimes in the Cimahi Police jurisdiction. The theories used in this research are criminology theory, rational choice theory, social control theory, planned behavior theory, communication theory, and social psychology theory. This research method was carried out through a qualitative approach, using data collection techniques through interviews, observation and data documentation. The research results show that cases of online fraud at the Cimahi Police are increasing along with technological developments and increasingly widespread internet connectivity. This crime has detrimental social and economic impacts on victims, including financial losses and psychological impacts. Therefore, appropriate steps are needed to increase public understanding of the risks and tactics of online fraud. A number of strategies that can be used to build public awareness in preventing online fraud crimes include: adopting a continuous education approach, strong public awareness campaigns need to be introduced through various media, collaboration with the private sector, especially e-commerce and banking platforms, developing complaint applications digital tools that enable people to report fraud easily and safely, adequate law enforcement training in digital investigations must be a priority, implementing victim protection programs, establishing partnerships with schools and integrating cyber security education in educational curricula, as well as conducting data analysis and prediction of online fraud trends the new one.